Development of Novel RGBW Mobile Display with Local Dimming Backlight System. Issue 1 (June 2014) - Harada, Tsutomu; Sakaigawa, Akira; Takasaki, Naoyuki; Goto, Fumitaka; Kimura, Susumu; Higashi, Amane; Nakahara, Tae; Shiraishi, Yasuhisa; Mifune, Masayuki
Abstract We have developed a new 7‐inch WQXGA RGBW mobile LCD with local dimming backlight technology. This panel achieves a 20% power reduction compared to that of the prior RGBW displays, with no image quality degradation. It also realizes contrast improvement and a total module thickness of 1.16mm.